Analisis Informasi Usaha melalui Google Maps dan Dampaknya terhadap Sistem Pencatatan Keuangan UMKM di Desa Aek Kota Batu - Pohan, Dinda Afrida; Iwan, Iwan; Fatahila, Mu'az Arbi; Pramaisela, Aisya Trixsi (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2026)
This study analyzes the use of Google Maps as a business information platform and its impact on the financial record-keeping systems of Micro, Small, and Medium Enterprises (MSMEs) in Aek Kota Batu Village. The study is grounded in MSME assistance activities conducted during the Community Service Program (Kuliah Kerja Nyata), which revealed increased business visibility through digital information, yet limited improvement in financial recording practices. The research aims to examine how Google Maps influences business information accessibility and its implications for MSMEs' financial record-keeping systems. A qualitative case study approach was employed through field observations, interviews with MSME owners, and documentation conducted during the KKN program. The findings indicate that Google Maps enhances customer reach and transaction intensity, which indirectly encourages MSMEs to begin implementing financial record-keeping practices, although these remain simple and unstandardized. The study offers empirical insights into the relationship between location-based business digitalization and the strengthening of MSMEs' financial management at the village level.